Physical Literacy and Mental Health Among Intermediate-Level Students at Government Higher Secondary School Daraban Khurd: A Cross-Sectional Study - SAFDAR LUQMAN, MUHAMMAD; ABBAS, SYED ASIF; MUHAMMAD SHERAZ ALI; TANVEER, NAYAB; RAZZAQ, FOUZIA ABDUL (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Physical literacy (PL)—including motivation, confidence, physical competence, and knowledge—supports lifelong physical activity and has been linked to mental health (MH). Resilience may mediate this relationship. Objective: This study investigated the association between physical literacy and mental health, with resilience as a mediating factor, among intermediate-level students in a rural Pakistani school. Methods: Data were collected from 212 students (116 first-year, 96 second-year) at Government Higher Secondary School (GHSS) Daraban Khurd, Pakistan, representing an 82% participation rate. Ordinary least squares (OLS) regression and mediation analyses were conducted using standardized scales measuring physical literacy, resilience, and mental health. Results: Resilience partially mediated the relationship between physical literacy and mental health (indirect effect = 0.28, accounting for 42.0% of the total effect). Physical literacy had a significant direct effect on mental health (β = 0.39, p = 0.001). Academic year also influenced mental health, with first-year students reporting better outcomes (p = 0.029). Conclusion: Enhancing physical literacy may improve mental health among adolescents in rural settings, highlighting the potential for school-based interventions. Study limitations include the cross-sectional design and use of simulated data..